The use of fecal calprotectin in the diagnosis of symptomatic uncomplicated diverticular disease in carbohydrate metabolism disorders - Dzvonkovska, Valentyna; Neiko, Vasyl; Salyzhyn, Tetiana; Feshovets, Nazar (ScienceRise: Medical Science, 2026)
Aim. To investigate the diagnostic value of fecal calprotectin levels in patients with isolated colonic diverticular disease and its combination with type 2 diabetes. Materials and methods. An open comparative cohort study was conducted, involving 60 individuals. The patients were divided into the following groups: 20 patients with verified colonic diverticular disease combined with type 2 diabetes, 10 patients with type 2 diabetes without intestinal lesions, 19 patients with isolated colonic diverticular disease, and a control group of 11 practically healthy individuals. To assess local inflammation in the intestinal wall, the level of fecal calprotectin was measured in all participants. Statistical processing included ROC analysis with the calculation of the Youden index to determine the optimal diagnostic accuracy thresholds. Results. It was established that the mean fecal calprotectin level in patients with colonic diverticular disease and concomitant type 2 diabetes was 152.90±57.14 μg/g, which significantly exceeded the values in patients with type 2 diabetes without colonic diverticular disease (68.40±24.65 μg/g). In the group of individuals with isolated colonic diverticular disease, the fecal calprotectin level was 125.26±46.13 μg/g. According to the ROC analysis, the use of the standard fecal calprotectin threshold value (>50.00 μg/g) in patients with concomitant type 2 diabetes leads to a sharp decrease in diagnostic specificity to 30.00 % while maintaining sensitivity at 100.00 %. The calculation of the Youden index demonstrated that increasing the threshold to 85.00 μg/g is optimal for this patient cohort. This increase allows for diagnostics with a sensitivity of 95.00% and a specificity of 80.00 %. For patients without concomitant metabolic pathology, using the 85.00 μg/g threshold also contributes to an increase in specificity to 90.91 %. Conclusions. The course of colonic diverticular disease with concomitant type 2 diabetes is accompanied by more pronounced local inflammation compared to the isolated form of the disease. To optimize diagnostics and prevent false-positive results in patients with concomitant carbohydrate metabolism disorders, it is advisable to increase the fecal calprotectin threshold value. Shifting the threshold to 85.00 μg/g ensures the restoration of the optimal balance of high sensitivity and specificity in both comorbid patients and individuals with isolated pathology